Implementasi Program Inovasi Pelayanan Berkelanjutan Inseminsi Buatan Dan Gangguan Reproduksi Sapi Di Kabupaten Pinrang - Baharuddin, Baharuddin; Ansari, Muh Isa; Tahir, Nurbiah (Universitas Muhammadiyah Makassar, 2020)
This study purposed to find out organizational and interorganizational behavior, lower level bureaucratic behavior, and the behavior of the target group towards the success of the service program for continuous innovation in artificial insemination and cow reproductive disorders in Pinrang Regency. The research method used qualitative. The number of informants in this study was 7 people. The data collection techniques were documentation, observation, and interviews. The results of the study showed that organizational and inter-organizational behavior determine the success of implementation through improvement / strengthening of organizational structure, collaborating between organizations, developing various inter-organizational interests and actions to achieve organizational goals, in this case the government for implementing sustainable service innovation programs for artificial insemination and reproductive disorders in Pinrang Regency.